Biomechanical principles applied to the Halliwick method of teaching swimming to physically handycapped individuals - Nicol, K.; Schmidt-Hansberg, M.; McMillan, J (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
In 1949 James McMillan taught a group of severely handicapped girls, most of whom were afflicted with cerebral palsy, to swim. The method that was devised and developed was named after the institution where it was originally developed-Halliwick School in London. Support for this venture was received from an orthopaedic surgeon, Oliver J. VaughanJackson, now a Visiting Professor at Newfoundland University. The method is now practiced in every continent of the world. In the development of the teaching technique, consideration was given to the various needs and abilities of the handicapped so that they could control the movement of their asymmetrical body shapes and densities. In this regard, no two people are alike. The physical requirements cannot be dissociated from mental reaction that may result from a situation involving loss of balance. By observing any child who is learning physical movement or an adult who is acquiring a new physical skill (e.g., ice skating), a noticeable pattern of human learning can be seen. It starts with a mental adjustment to the elements or environment of the activity. This is followed by efforts in gross patterns of movement, which can be referred to as balance restoration. Success in this phase leads to the prevention of movement while holding a starting position or posture-inhibition. Finally, a mentally pleasing and physically controlled movement-facilitation-is accomplished.